Entrepreneurial potentials of tourism villages in Bantul Regency, Yogyakarta - Ajie Wicaksono; John JOI Ihalauw; Sony Heru Priyanto (Privietlab, 2026)
Tourism villages in Yogyakarta, Indonesia, promote economic diversification, cultural preservation, and community empowerment. However, research lacks connection between heritage and innovative business strategies, affecting livelihoods. This research aims to explore the connection between cultural heritage and innovative business strategies in tourism villages in Yogyakarta, Indonesia, focusing on sustainable livelihoods and entrepreneurial ecosystems. The study employed VOSviewer analysis and a systematic literature review to explore entrepreneurial potential in tourism villages in Bantul Regency, utilizing Scopus and Google Scholar databases by using Publish or Perish application. 41 research articles were derived after conducting PRISMA analysis with some inclusion and exclusion criteria. The results show that the network visualization shows a central hub of medium to large-sized nodes, including